FOEHN OVER THE EASTERN CARPATHIANS, CHARACTERISED BY A WESTERN CIRCULATION OF ANTICYCLONIC SHADE. CASE STUDY, 4–6 FEBRUARY, 2011 - VIORICA DIMA (Revue Roumaine de Géographie)
This paper explores the characteristics of an air mass crossing a mountain obstacle oriented perpendicularly to the air circulation direction, inducing foehn effects on its lee side. After a brief presentation of the general concepts from the specialist literature concerning the occurrence of foehn, this analysis focuses on the particular situation of February 4–6 2011, characterised by a western circulation of anticyclonic nuance, which the northern massifs of the Eastern Carpathians were subjected to, triggering foehn effects in Moldavia. The behaviour of the main meteorological characteristic of the air mass crossing the orographic barrier was interpreted on the grounds of the vertical profiles obtained with the Non-Hydrostatic Mesoscale Model (NMM) numerical model. Thus, the vertical distribution of relative moisture, cloudiness and air temperature, as well as the wind vertical profile on both sides of the mountain obstacle were analysed. Using the data from in situ observations over the interval of concern and the diagnostic maps plotted at the National Meteorological Administration (NMA), the differences found in the temperature and precipitation distribution between the windward and leeward sides of the mountain obstacle were highlighted.